Preparation and quantification of the total phenolic products in Citrus fruit using solid‐phase extraction coupled with high‐performance liquid chromatography with diode array and UV detection. Issue 19 (7th September 2016) - Zeng, Honglian; Liu, Zhenli; Zhao, Siyu; Shu, Yisong; Song, Zhiqian; Wang, Chun; Dong, Yunzhuo; Ning, Zhangchi; He, Dan; Wang, Menglei; Lu, Cheng; Liu, Yuanyan; et al.
Abstract : Citrus fruit is an important health‐promoting food that is rich in dietary phenolic metabolites. Traditional Chinese medicines, such as Zhishi and Zhiqiao, come from young and immature fruits of Citrus cultivars. The preparation of diversified bioactive phenolic products and establishment of the corresponding quality control methodology are challenging and necessary. In the current study, four types of solid‐phase extraction sorbents for the enrichment and clean‐up of the phenolic matrix were evaluated. A solid‐phase extraction column coated with Strata‐X was finally used in the procedure. Twenty phenolic compounds were selected to evaluate the extraction performances of the sorbents using high‐performance liquid chromatography analysis. Under the optimized conditions, good linearities were obtained with R 2 more than 0.9996 for all analytes with LODs of 0.04–1.012 μg/g. Intra‐ and interday relative standard deviation values were less than 3%, and the recovery was equal to or higher than 90.02%. Compared to non‐solid‐phase extraction process, the content of total phenolic products was elevated 35.55–68.48% with solid‐phase extraction. Finally, the developed and validated method was successfully applied to the discrimination of Zhishi samples from different species as well as Zhishi and Zhiqiao samples in different development stages.